Disruptions and bridges in rural Australia: higher education aspiration to expectation of participation. Issue 3 (16th April 2019) - Kilpatrick, Sue; Katersky Barnes, Robin; Heath, Jennifer; Lovat, Alex; Kong, Wee-Ching; Flittner, Nicholas; Avitaia, Samantha
ABSTRACT: Widening higher education participation can deliver benefits to individuals, societies and economies but rural populations experience factors which inhibit their aspiration for and participation in higher education. When designing outreach programs, universities need to consider this landscape of factors, many of which are socio-cultural. This article reports evaluation results from a project that trialled three university outreach programs designed to align with rural contexts with the aim of identifying aspects which were effective in addressing factors of rurality, revealing obscured future options and showing higher education pathways as attainable. Universities can work effectively with rural communities to inform people's higher education aspirations through 'disruptions', interventions that inform educational aspiration, and 'bridges' which support higher education participation through facilitating access to information, physical, financial, academic and social resources. A model including both 'disruptions' and 'bridges', jointly resourced and drawing on social capital resources of communities and higher education institutions is presented.